New Insights into Acylhydrazones E/Z isomerization: An Experimental and Theoretical Approach. - Fernández-Palacios, Sara; Matamoros, Esther; Morato Rojas, Isabel; López Navarrete, Juan T.; Ruiz-Delgado, María del Carmen; Vida-Pol, Yolanda; Perez-Inestrosa, Ezequiel (MDPI, 2023)
A family of acylhydrazones have been prepared and characterized with the aim of investigating their potential as information storage systems. Their well stablished synthetic methodologies allowed the preparation of seven chemically stable acylhydrazones in excellent yields, that have been photophysically and photochemically characterized. In addition, DFT and TD-DFT calcula-tions have been performed to gain more insights into the structural, energetics and photophysi-cal properties of the E/Z isomers. Our results reveal that the E,Z configurational isomerization upon irradiation is highly dependent on the stabilization of the E or Z isomer due to the for-mation of intramolecular H bonds and electronic/steric effects intrinsically related to their structures. In addition, Raman spectroscopy is also used to confirm molecular structural changes after the formation of hydrogen bonds in the isomers
Publicación en Open Acces. https://www.mdpi.com/1422-0067/24/19/14739
Keywords: Fotoquímica; isomerización E/Z fotoquímica